A hypothesis about the influence of oxidative stress on amino acid protein composition during evolution - González-Tortuero, Enrique; Rodríguez-Rojas, Alexandro (Frontiers in Ecology and Evolution, 2023)
Life emerged in an anoxic world, but the release of molecular oxygen, the by -product of photosynthesis, forced adaptive changes to counteract its toxicity. However, reactive oxygen species can damage all cellular components, including proteins. Therefore, several mechanisms have evolved to balance the intracellular redox state and maintain a reductive environment more compatible with many essential biological functions. In this study, we statistically interrogated the amino acid composition of E. coli proteins to investigate how the proneness or susceptibility to oxidation of amino acids biased their sequences. By sorting the proteins into five compartments (cytoplasm, internal membrane, periplasm, outer membrane, and extracellular), we found that various oxidative lesions constrain protein composition and depend on the cellular compartments, impacting the evenness of distribution or frequency. Our findings suggest that oxidative susceptibility could influence the observed differences in amino acid abundance across cellular compartments. This result reflects how the oxidative atmosphere could restrict protein amino acid composition and impose a codon bias trend.